TRANSFORMASI SUMBER DAYA MANUSIA DAN ORGANISASI DALAM MENGHADAPI PERSAINGAN BISNIS - Ni Putu Nursiani (Universitas Nusa Cendana, 2015)
Rapid change in an organization is an external power that caused a transformation. Basicly, mainpurpose in that transformation is to change the organization structure to be more flexible andcompetitive in smaller structural level and fewer number of managers and employees.Comprehensively transformation should be applied to overcome members rejection, so that theorganization must find the solutions to reduce that barriers. Organization should learn aboutdiverse of organization members culture and value, developing its own organization culture througheffective communication. To support the development of organization culture, it must be a change inhuman resources policy. Keywords: HR Transformation, Organization transformation and business competition